Metastatic clear-cell renal cell carcinoma: a frequent NOTCH1 mutation predictive of response to anti-NOTCH1 CB-103 treatment - Thi Oanh Bui; Eurydice Angeli; Morad El Bouchtaoui; Guillaume Gapihan; Van Tu Dao; Justine Paris; Christophe Leboeuf; Michael Soussan; Patrick Villarese; Marianne Ziol; Emmanuel Van Glabeke; Thi Huong Le; et al. (Experimental Hematology & Oncology, 2023)
Abstract Background Clear-cell renal cell carcinomas (ccRCCs) are malignant tumors with high metastatic potential and resistance to treatments occurs almost constantly. Compared to primary tumors, there are still limited genomic data that has been obtained from metastatic samples. Methods We aimed to characterize metastatic ccRCC by way of whole-genome analyses of metastatic formalin-fixed samples, using OncoScan® technology. We identified a frequent, unexpected pL1575P NOTCH1 mutation which we set out to characterize for translational purposes. We thus implemented patient-derived xenografts from metastatic samples of human ccRCC to explore its clinical significance. Results We showed that pL1575P NOTCH1 mutation was an activating mutation, leading to the expression of NOTCH1-intracellular domain-active fragments in both cancer cells and tumor endothelial cells, suggesting a trans-differentiation of cancer cells into tumor micro-vessels. We demonstrated that this mutation could be used as a predictive biomarker of response to CB-103, a specific NOTCH1-intracellular domain inhibitor. One striking result was the considerable anti-angiogenic effect, coherent with the presence of NOTCH1 mutation in tumor micro-vessels. Conclusions We identified a frequent, unexpected pL1575P_c4724T_C NOTCH1 mutation as a new biomarker for ccRCC metastases, predictive of response to the CB103 NOTCH1-intracellular domain inhibitor.